Using an integrated knowledge translation or other research partnership approach in trainee-led research: a scoping review protocol. Issue 5 (25th May 2021) - Cassidy, Christine E; Beck, Amy Jane; Conway, Aislinn; Demery Varin, Melissa; Laur, Celia; Lewis, Krystina B; Ramage, Emily R; Nguyen, Tram; Steinwender, Sandy; Ormel, Ilja; Stratton, Lillian; Shin, Hwayeon Danielle
Abstract : Introduction: Collaborative research approaches, such as co-production, co-design, engaged scholarship and integrated knowledge translation (IKT), aim to bridge the evidence to practice and policy gap. There are multiple benefits of collaborative research approaches, but studies report many challenges with establishing and maintaining research partnerships. Researchers often do not have the opportunity to learn how to build collaborative relationships, and most graduate students do not receive formal training in research partnerships. We are unlikely to make meaningful progress in strengthening graduate and postgraduate training on working collaboratively with the health system until we have a better understanding of how students are currently engaging in research partnership approaches. In response, this scoping review aims to map and characterise the evidence related to using an IKT or other research partnership approach from the perspective of health research trainees. Methods and analysis: We will employ methods described by the Joanna Briggs Institute and Arksey and O'Malley's framework for conducting scoping reviews. The reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for scoping reviews checklist. We will include both published and unpublished grey literature and search the following databases: MEDLINE, Embase, CINAHL, PsycINFO, ProQuest Dissertations & Theses Global databases, Google Scholar and websites from professional bodies and other organisations. Two reviewers will independently screen the articles and extract data using a standardised data collection form. We will narratively describe quantitative data and conduct a thematic analysis of qualitative data. We will map the IKT and other research partnership activities onto the Knowledge to Action cycle and IAP2 Levels of Engagement Framework. Ethics and dissemination: No ethical approval is required for this study. We will share the results in a peer-reviewed, open access publication, conference presentation and stakeholder communications.